Results of liver and spleen endoscopic ultrasonographic elastography predict portal hypertension secondary to chronic liver disease - Robles-Medranda, Carlos; Oleas, Roberto; Puga-Tejada, Miguel; Valero, Manuel; Valle, Raquel Del; Ospina, Jesenia; Pitanga-Lukashok, Hannah (Endoscopy International Open, 2020)
Background and study aims Assessment of endoscopic ultrasonography (EUS)-elastography of the liver and spleen may identify patients with portal hypertension secondary to chronic liver disease. We aimed to evaluate use of EUS-elastography of the liver and spleen in identification of portal hypertension in patients with chronic liver disease.Patients and methods This was a single-center, diagnostic cohort study. Consecutive patients with liver cirrhosis and portal hypertension underwent EUS-elastography of the liver and spleen. Patients without a history of liver disease were enrolled as controls. The primary outcome was diagnostic yield of liver and spleen stiffness measurement via EUS-elastography in prediction of portal hypertension secondary to chronic liver cirrhosis. Cutoff values were defined through Youden’s index. Overall accuracy was calculated for parameters with an area under the receiver operating characteristic (AUROC) curve ≥ 80 %. Results Among the 61 patients included, 32 had cirrhosis of the liver. Liver and spleen stiffness was measured by the strain ratio and strain histogram, with sensitivity/(1 − specificity) AUROC values ≥ 80 %. For identification of patients with cirrhosis and portal hypertension, the liver strain ratio (SR) had a sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of 84.3 %, 82.8 %, 84.4 %, and 82.8 %, respectively; the liver strain histogram (SH) had values of 87.5 %, 69.0 %, 75.7 %, and 83.3 %, respectively. EUS elastography of the spleen via the SR reached a sensitivity, specificity, PPV, and NPV of 87.5 %, 69.0 %, 75.7 %, and 83.3 %, respectively, whereas the values of SH were 56.3 %, 89.7 %, 85.7 %, and 65.0 %, respectively. Conclusion Endoscopic ultrasonographic elastography of the liver and spleen is useful for diagnosis of portal hypertension in patients with cirrhosis.